Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1620/tjem.236.225
|View full text |Cite
|
Sign up to set email alerts
|

Mitochonic Acid 5 (MA-5), a Derivative of the Plant Hormone Indole-3-Acetic Acid, Improves Survival of Fibroblasts from Patients with Mitochondrial Diseases

Abstract: Mitochondria are key organelles implicated in a variety of processes related to energy and free radical generation, the regulation of apoptosis, and various signaling pathways. Mitochondrial dysfunction increases cellular oxidative stress and depletes ATP in a variety of inherited mitochondrial diseases and also in many other metabolic and neurodegenerative diseases. Mitochondrial diseases are characterized by the dysfunction of the mitochondrial respiratory chain, caused by mutations in the genes encoded by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 26 publications
2
58
0
1
Order By: Relevance
“…Here, we report that a newly synthesized indole acetic acid (IAA) derivative, mitochonic acid 5 (MA-5), 5 targets the mitochondrial protein mitofilin and facilitates ATP production, protecting against AKI and renal respiration damage in Mitomice. Our finding changes the focus of the search for drugs for mitochondrial and mitochondrial-related renal diseases, such as AKI, CKD, and SRNS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report that a newly synthesized indole acetic acid (IAA) derivative, mitochonic acid 5 (MA-5), 5 targets the mitochondrial protein mitofilin and facilitates ATP production, protecting against AKI and renal respiration damage in Mitomice. Our finding changes the focus of the search for drugs for mitochondrial and mitochondrial-related renal diseases, such as AKI, CKD, and SRNS.…”
mentioning
confidence: 99%
“…Recently, we have reported that MA-5 increased the cellular ATP level and the improved survival of fibroblasts from patients with mitochondrial diseases. 5 Thus, MA-5 might protect tubular cells from IRI by cisplatin by maintaining intracellular ATP levels.…”
mentioning
confidence: 99%
“…MA-5 targets the mitochondrial protein mitofilin at the crista junction of the inner membrane and can be a novel agent for treating diseases associated with mitochondrial dysfunction [5,6] . In patients with SD having Bell's palsy, mitochondrial cytopathy may develop with ATP synthesis impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Сама β-индолилуксусная кислота оказывает туморо-токсический ýффект из-за повреждения ДНК клеток [28,29]. Одно из производных β-индо-лилуксусной кислоты, митохониевая кислота, оказывает защитное воздействие на фибробла-сты, полученные от больных с нейродегенера-тивной патологией, вероятнее всего благодаря олигомеризации АТФ-синтазы и последующей продукции большего количества АТФ [30]. По-ражение митохондрий является одним из вероят-ных патогенетических механизмов, приводящих к развитию болезни Паркинсона.…”
Section: Discussionunclassified